Percutaneous autologous bone marrow transplantation for the treatment of delayed union of limb bone in children - Wu J; Guo HX; Liu X; Li M; Cao YJ; Qu XY; Zhou H; Weng LQ (Dove Medical Press, 2018)
Jun Wu,* Hongxi Guo,* Xing Liu, Ming Li, Yujiang Cao, Xiangyang Qu, Hai Zhou, Liuqi Weng Department of Orthopaedics, Children’s Hospital of Chongqing Medical University, Ministry of Education Key Laboratory of Child Development and Disorders, Chongqing Engineering Research Center of Stem Cell Therapy, China International Science and Technology Cooperation Base of Child Development and Critical Disorders, Chongqing, People’s Republic of China *These authors contributed equally to this work Background and purpose: Percutaneous autologous bone marrow transplantation (PABMT) is a minimally invasive therapeutic strategy for the treatment of delayed bone union in adults, which has been confirmed by many studies. However, there is no report on PABMT application in pediatric orthopedic surgery. The aim of this article was to analyze the therapeutic effect of PABMT in children with delayed union of limb bone and its influence in relation to delayed bone union therapy, transplantation period, patients’ sex, fracture location, and fracture fixation.Methods: In this study, 53 patients (aged 3–16 years, with an average age of 6.7 years) with delayed union of long bone (20 femurs, 12 tibiae, 10 humeri, 5 radiuses, 5 ulnas, and 1 fibula) were treated using PABMT. Clinical examination and X-ray were integrated to evaluate the therapeutic effect.Results: All 53 patients were followed up for 2–6 years (average time, 3.5 years). Of the 53 patients, 47 (88.7%) were healed, whereas the other 6 (11.3%) were not, and were subsequently treated by autologous bone grafting. In 30 patients who received their first PABMT treatment 6–8 months after fixation, the clinical cure rate, operation times, and healing time were 83.3%, 5.8±0.5 months, and 2.5±0.6, respectively. In the other 23 patients, whose first PABMT treatments were started within 4 to 6 months after fixation, the clinical cure rate, operation times, and healing time were 95.7% (P=0.167), 3.2±0.3 months (P=0.001), and 1.3±0.6 (P=0.001), respectively. The patients’ sex, fracture location, and fracture fixation did not have statistical influence on the clinical efficacy.Conclusion: PABMT is a minimally invasive and effective strategy for the treatment of delayed union of limb bone in children. The early surgical treatment facilitates the fracture healing, reduces the number of transplantation, and shortens the course of treatment. Keywords: fracture, minimally invasive, medulla ossium, mesenchymal stem